1975
DOI: 10.2113/gsecongeo.70.3.431
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide deformation studies; III, Experimental deformation of chalcopyrite to 2,000 bars and 500 degrees C

Abstract: Single crystals and aggregates of natural chalcopyrite were deformed under controlled conditions of temperature (24 ø to 500øC), confining pressure (500 to 2,000 bars), and strain rate (constant 7.2 X 10 -5 sec -•) in several series of experiments designed to test the deformational properties of this mineral under shallow tectonic conditions. At low temperature, chalcopyrite deforms by cataclasis combined with translation gliding on (112) (510) and (112) (0:•1). Polysynthetic deformation twinning, also on (112… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

1980
1980
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 11 publications
1
22
0
2
Order By: Relevance
“…17d). Pyrrhotite, chalcopyrite, sphalerite and galena in the sulphide bodies at Sulitjelma generally show evidence of ductile deformation, as would be predicted from experimental studies (Clark and Kelly, 1973;Kelly and Clark, 1975). The cases in which brittle fracturing of chalcopyrite and sphalerite has been observed are probably the result of post-D3 deformation under conditions below the brittle-ductile transition boundaries for these minerals.…”
Section: Mineralogy and Microscopic Features Of Deformationsupporting
confidence: 61%
See 2 more Smart Citations
“…17d). Pyrrhotite, chalcopyrite, sphalerite and galena in the sulphide bodies at Sulitjelma generally show evidence of ductile deformation, as would be predicted from experimental studies (Clark and Kelly, 1973;Kelly and Clark, 1975). The cases in which brittle fracturing of chalcopyrite and sphalerite has been observed are probably the result of post-D3 deformation under conditions below the brittle-ductile transition boundaries for these minerals.…”
Section: Mineralogy and Microscopic Features Of Deformationsupporting
confidence: 61%
“…These are shown in Fig. 6 onto which are also superimposed the brittle-ductile transformation boundaries for the main sulphide minerals based on experimental data from Kelly (1973), Salmon et al (1974), Atkinson (1975), Kelly and Clark (1975) and Cox et al (1981), together with the fields of greenschist and amphibolite grade metamorphism. The brittle-ductile boundaries for the sulphides are maximum values due to the disparity between experimental strain rates and geologically realistic strain rates which are several orders of magnitude lower.…”
Section: Metamorphic History Of the Oresmentioning
confidence: 84%
See 1 more Smart Citation
“…Hence, pyrite withstands deformation far better than most of the other typically associated sulphides, as shown in Fig. 2 Graf and Skinner (1970), Atkinson (1975), and Kelly and Clark (1975).…”
Section: Physical Properties Of Pyritementioning
confidence: 89%
“…The response of individual ore minerals to deformation varies widely, depending on the conditions of deformation and on their own physical properties (e.g., pyrite is much harder than most other sulfides and withstands deformation, whereas softer minerals flow plastically or are dissolved by pressure solution). Kelly & Clark (1975) showed that the strengths of several of the common sulfide minerals decrease significantly as temperature rises, making them more susceptible to plastic deformation at higher grades of metamorphism. More refractory sulfide and oxide minerals retain their strength in spite of rising temperature at most moderate metamorphic grades and are thus more likely to survive periods of deformation and to retain physical and chemical textures.…”
Section: Deformation and Metamorphismmentioning
confidence: 99%